Antennas For Non-Terrestrial Networks - De Marco, Raffaele; Fortino, Giancarlo; Boccia, Luigi (Università della Calabria, 2024)
This doctoral thesis focuses on antennas for Non-Terrestrial Networks (NTN) and satellite communications, showcasing two innovative antenna designs. First, a novel design for 2-D electronically steerable parasitic array radiator (ESPAR) is presented. This design is based on a 3×3 microstrip patch antenna array and it is intended to serve as a subarray within clustered phased array architecture. Compared to the existing varactor-based 2-D ESPAR designs, the proposed solution allows a continuous beam steering along eight different azimuthal planes, thus, extending the beam scanning capabilities to a conical region. Encouraged by the promising results, the concept is further extended into the Ka-band through integration into a large array configuration. This extension underscores the adaptability and practical viability of the proposed antenna concepts, paving the way for advancements in NTN and satellite communication technologies. The second contribution involves the design of an innovative dual-band dual-polarized transmitarray antenna (TA) utilizing multilayer frequency selective surfaces (MFSS) operating at K/Ka band. The proposed design achieves an optimal compromise between aperture efficiency and thickness, compared to the existing dual-band dualpolarized transmitarrays. This design approach allows for a cost-effective and lowprofile implementation, utilizing a single multilayer PCB without any air gap or vertical transition. An equivalent circuit model for the unit-cell has been formulated and examined, offering insights into the optimal phase control methodology and the transmission mechanism. The proposed design incorporates DL and UL unit-cells that are interleaved and autonomously control the transmitted phase for each band and polarization. Moreover, the proposed unit-cell and transmitarray are versatile, capable of scaling with varying frequencies, making them suitable for implementing other dual-band transmitarrays operating in two distinct frequency bands characterized by a substantial difference in upper and lower frequencies.
Università della Calabria. Dipartimento in Ingegneria Informatica, Modellistica, Elettronica e Sistemistica. Dottorato di ricerca in: Information and Communication Technologies (ICT) Ciclo XXXVI
Keywords: non-terrestrial networks; ESPAR; Transmitarray; metasurfaces; hybrid antennas